Animate CC: Storyboarding. - O' Connor, Dermot (linkedin.com, 2017)
Discover how to set up a storyboard in Adobe Animate CC. Learn how to do fades and cross dissolves, create vertical pan shots, pose characters, add and edit audio, and more.